2020
DOI: 10.1017/s0033291720002858
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of specific cognitive functions and associations with schizophrenia spectrum disorders using CANTAB: a nation-wide twin study

Abstract: Background Many cognitive functions are under strong genetic control and twin studies have demonstrated genetic overlap between some aspects of cognition and schizophrenia. How the genetic relationship between specific cognitive functions and schizophrenia is influenced by IQ is currently unknown. Methods We applied selected tests from the Cambridge Neuropsychological Test Automated Battery (CANTAB) to examine the heritability of specific cognitive functions and associations with schizop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Although some studies report the mediating role of cognitive abilities between the GPS and psychopathology in children 16,25 , such approaches have failed to address the potential environmental mechanisms behind this relationship [26][27][28] . Thus, the comprehensive causal trajectories between genes, the environment, intelligence, and psychotic disorders remain unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies report the mediating role of cognitive abilities between the GPS and psychopathology in children 16,25 , such approaches have failed to address the potential environmental mechanisms behind this relationship [26][27][28] . Thus, the comprehensive causal trajectories between genes, the environment, intelligence, and psychotic disorders remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it was not until recently that researchers have drawn systematic research into the relationship between cognition and psychotic disorders in early childhood. Although some studies report the mediating role of cognitive abilities between the GPS and psychopathology in children 16, 25 , such approaches have failed to address the potential environmental mechanisms behind this relationship 2628 . Thus, the comprehensive causal trajectories between genes, the environment, intelligence, and psychotic disorders remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…For OCD patients, planning deficits involving flexible self-ordered spatial sequencing are correlated with decreased resting state and functional connectivity between the lPFC and putamen ( Vaghi et al, 2017a,b ). For schizophrenia, similar dysconnectivity between lPFC and basal ganglia has been shown ( Zhou et al, 2007 ) as well as impairments in planning and sequencing tasks with heritable components apparently independent of IQ ( Lemvigh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 82%
“…More twin studies of social cognition are needed, including examinations of other domains of social cognition 7 . Previous twin studies of cognition have suggested that the basic genetic architecture of schizophrenia shows overlap with cognition [10][11][12] , and therefore future studies should examine potential genetic associations between social cognition and schizophrenia liability and how this cognitive domain relates to IQ to further understand the genetic underpinnings of social cognitive deficits in schizophrenia. A better understanding of the pathophysiological processes underlying cognitive impairments in schizophrenia spectrum disorders may increase our understanding of the aetiology of the illness leading from genes to psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…Social cognition is also impaired in first-degree relatives of patients with schizophrenia, suggesting that these deficits may be related to the genetic vulnerability of the disorder 8 . Previous twin studies have established that most cognitive functions are strongly influenced by genetics 9 and show genetic overlap with schizophrenia liability, indicating that shared genetic factors influence cognition and schizophrenia risk [10][11][12] . However, twin studies of social cognition in schizophrenia are lacking 9,13 .…”
Section: Introductionmentioning
confidence: 99%